Mental Health Promotion Efforts in the Switch-Up Program in Collaboration with the Indonesian Mental Health Foundation (YSMI) - Tiara Pascanoviera Robaeni; Hanny Hafiar (COMMUNICATION MAJOR, 2022)
Mental health problems can be handled by promoting mental health to the community, as was done in the Switch-Up program in collaboration with the Indonesian Mental Health Foundation (YSMI). The activities carried out are expected to build awareness about the importance of maintaining mental health and the need to be treated if affected by mental health disorders. Departing from the conceptual basis of health promotion and the theoretical basis of symbolic interaction, the researcher obtained a typification as the purpose of this study was to find out how mental health promotion efforts were carried out by the Switch-Up program in collaboration with YSMI. The basic procedure used is qualitative approach, constructivism paradigm, case study type by collecting data through observation, in-depth interview with purposive sampling technique, documentation and literature study. The data analysis and data validity test by data triangulation. The results of this study, the Switch-Up program activity with YSMI on its part made activities that contained providing education about mental health through various activities, mental health check-ups and know your strength. integrated health services from promotive, preventive, rehabilitative and curative efforts. In addition, with YSMI's collaboration, the participants and clients have a stronger belief because it brings out the figure of Dr. Rama Giovani SpKJ as the icon of the Switch-Up program and the treatment process for mental health problems can be followed up both in terms of consultations to medicines by more professionals in their fields. In conclusion, mental health promotion needs to be implemented in an integrated manner so that the fulfillment of needs in dealing with mental health problems can be met.